Nigeria beats China - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Nigeria has become the main supplier of sesame to Japan, pushing China into the second place, and taking one whole quarter of the market share. In 2001, Nigeria exported more than 34,000 t of sesame to Japan, 57% more than in 2000, and just more...